Sex- and Subtype-Related Differences in the Comorbidity of Adult ADHDs. (October 2016) - Groß-Lesch, Silke; Dempfle, Astrid; Reichert, Susanne; Jans, Thomas; Geissler, Julia; Kittel-Schneider, Sarah; Nguyen, Thuy Trang; Reif, Andreas; Lesch, Klaus-Peter; Jacob, Christian Peter
Objective: Comorbidity in adult ADHD (aADHD) has been investigated in a large number of studies using varying research approaches with divergent results. In contrast, there is limited information about sex- or subtype-related differences from studies with small sample size.Method: A large sample of 910 individuals (458 males, 452 females) affected with aADHD was recruited at a tertiary referral center. All probands underwent a four-step procedure for diagnosing aADHD, including the Structured Clinical Interview of Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV ) Axis I disorders to assess comorbidity. This study will provide additional information regarding the co-morbidity of Axis I disorders in the currently largest clinical referral sample. However, the main objective of this study is to gain information about sex- or subtype-related differences.Results: Affected females show higher rates of mood (61% vs. 49%), anxiety (32% vs. 22%), and eating disorders (16% vs. 1%) than affected males, while substance use disorders were more frequent in affected males (45% vs. 29%), which mirrors sex differences in prevalence in the general population. There were hardly any relevant differences in comorbidities between subtypes, with the exception of the inattentive subtype having an especially low prevalence of panic disorder. Comorbidity in general and substance use disorders in particular, but not sex or subtype, were highly predictive of lower psychosocial status.Conclusion: Sex-related differences in the comorbidity of aADHD are more pronounced than subtype-related differences.